Pengaruh model pembelajaran problem based learning berbantuan media digital terhadap hasil belajar kognitif matematika peserta didik kelas IV sekolah dasar - Windi Astuti; Jenny Indrastoeti Siti Poerwanti; Chumdari Chumdari (Universitas Sebelas Maret, 2024)
The purpose of this research is to 1) describe how implementation of problem based learning model with digital media on mathematics study. Also, the purpose of this research is to 2) determine the differences between cognitive learning outcomes which taught using digital media-assisted problem based learning model and digital media-assisted guided inquiry model. This research used an experimental approach by pretest-posttest control group design. The population were students of fifth-grade elementary school in academic year 2023/2024 at Banjarsari District, Surakarta City. The sample was taken in the manner of cluster random sampling technique. Data collection technique were using tests and observation. Based on analysis data, it can conclude that 1) teachers taught problem based learning model with digital media-assisted on mathematics study appropriate on the syntax, 2) mathematics cognitive learning outcomes of students which taught with problem based learning model get better outcomes than guided inquiry model in measurment area and volume topics.